Platyhelminthes of common buzzard (Buteo buteo): Checklist of species in Europe and new parasite-host associations in Romania - Katarzyna Anna Hołówka; Angela Monica Ionică; Mihai Ilea; Alexandru Cristian Poșa; Vlad Dan Cotuțiu; Alexandru Bulacu; Jilji Sitko; Oana Cristina Vasiliu; Andrei Daniel Mihalca; Călin Mircea Gherman (International Journal for Parasitology: Parasites and Wildlife)
Background: Platyhelminthes are common parasites of diurnal birds of prey, including common buzzard (Buteo buteo). They are widely distributed in Europe. Despite the extensive study of flatworms across the continent, this study represents the first report for Romania and extends the biogeographic knowledge of Platyhelminthes in diurnal raptors. It also identifies common buzzards as a new host of Parastrigea flexilis in Europe. Materials and methods: Between 2017 and 2020, 63 common buzzards (Buteo buteo) found road killed or dead due to other causes were collected from Romania. All specimens were necropsied and examined for internal helminths, which were preserved in ethanol for molecular identification and formaldehyde for morphological identification. Results: Species identified included Cestoda: Cladotaenia globifera (33.3%) and five species of Trematoda: Neodiplostomum attenuatum (12.7%), Strigea falconis (6.4%), Parastrigea flexilis (3.2%), Neodiplostomum spathoides (3.2%) and Brachylaima fuscata (1.6%). Conclusions: This study provides new data about diversity, phylogenetics and geographical distribution of Platyhelminthes parasitizing Buteo buteo in Romania. To our best knowledge, it identifies B. buteo as a new host of Parastrigea flexilis and reports the first genetic sequence of Neodiplostomum spathoides.